Islam kontemporer dan moderasi beragama: studi kasus radikalisasi di Sumatera Utara - Muthiatul Khairiyah; Amru Abdul Wadud; Amriansyah Pohan; Rizkiyah Purnama (Indonesian Counselor Association (IKI), 2024)
This research aims to analyze the contemporary reality of Islam in Indonesia, focusing on the challenges of radicalization and the importance of religious moderation, as well as efforts to maintain inter-religious and ethnic harmony in North Sumatra. The research also explores the ethnic and religious diversity of the province, which is inhabited by various tribes such as Malay, Minangkabau, Acehnese, Batak and others. In facing the challenges of radicalization and extremism, religious moderation is considered the right solution. Moderate Islam, which emphasizes tolerance, peace and respect for differences, is an important foundation for preventing violence in the name of religion. This research uses a literature review method with a deductive approach. The data used is secondary literature, which includes studies on ethnic diversity, religion, and the phenomenon of radicalization in North Sumatra. The results show that religious moderation can be an effective strategy to strengthen social integration and reduce the potential for sectarian conflict in the area. The contribution of this research is to provide new insights into the importance of religious moderation in the Indonesian context, especially in North Sumatra, as well as its impact in overcoming the challenges of radicalization. This research is expected to provide policy recommendations to strengthen interfaith harmony in Indonesia.